Implementation Of Project Based Learning (PjBL) Models In Science Learning In Elementary Schools - Erika Erika (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The purpose of this study is to describe the Project Based Learning learning model in science learning. By looking at the definitions, steps, advantages and disadvantages as well as the implementation of the PjBL learning model in science learning, it is hoped that it will bring new insights into the application of the learning model. The research method used is descriptive qualitative through literature study by reviewing books, articles, journals, and other sources of information that are relevant to PjBL and the independent curriculum. From this literature study it was found that PjBL is a good and appropriate learning strategy because PjBL has the advantage of being able to improve learning outcomes, achievement, motivation, and the 4C abilities (collaboration, communication, critical thinking, creative thinking) of students. The results of the research show that the Project Based Learning model is a very good model to use in science learning. This can be seen from the many learning theories that support project-based learning models in science learning.